La traiettoria storica dell’Etiopia di Meles Zenawi: Fra democrazia rivoluzionaria, federalismo etnico e Stato sviluppista - Cellai, Andrea (Premio Cesare Alfieri «Cum Laude», 2022)
The present study analyzes the historical framework of contemporary Ethiopia. Particular attention is given to the economic and political events from the regime change in 1991 to the death of TPLF leader Meles Zenawi in 2012. In line with the Braudelian historical analysis three aspects will be taken into consideration: the Ethiopian Empire under Haile Selassie’s rule, the Ethiopian Revolution of 1974, with the rise to power of the Soviet-aligned Derg, and the ensuing civil war with the Maoist guerillas of the TPLF. In addition, the TPLF regime will be examined according to its three underlying concepts – revolutionary democracy, ethnic federalism, and developmental state – and defining theories – neo-patrimonialism, vanguard capitalism, and political marketplace.